Stakeholder Attitudes Toward Student Drug Testing - Jordan, John (2019)
The purpose of this study was to identify the attitudes toward mandatory student drug testing from various school stakeholder groups in a Small Rural Southeast Georgia School District. This study employed a quantitative methodological research design along with descriptive analyses of two research questions for the sixth through twelfth grade population of students, parents, and school personnel. Survey data from the middle and high school stakeholder groups were received during the fall of 2019 and analyzed to determine the overall attitude toward the use of student drug testing as well as the differences that existed among various stakeholder groups. This study focused on two overarching research questions with the first being: what are the overall attitudes of middle and high school faculty/staff, administrators, parents, and students regarding mandatory student drug testing for the school district; and the second question being: to what extent do stakeholder attitudes toward mandatory student drug testing vary according to gender, ethnicity, grade cluster, exposure to experiences related to mandatory drug testing and involvement in extracurricular activities? The survey revealed the overall attitudes of grades 6-8 and grades 9-12 students, parents, and school personnel had high agreeability with the use of Mandatory Random Student Drug Testing (MRSDT). The scoring results of three main survey variables; necessity of drug testing, negative perceptions of drug testing, and positive results from drug testing, all suggests that this survey population agreed with the policy and indicated an interest in continuing MRSDT in grades 9-12 and expanding to grades 6-8. While there was high agreeability from all stakeholders toward MRSDT, two statistically significant differences existed in this study. Grades 6-8 indicated a greater need for drug testing than grades 9-12, and Persons of Color Subgroup had greater negative perceptions toward MSRDT than the White Subgroup. This study impacts local educational leaders and stakeholders by vetting the current policy and the desires to have MRSDT as a part of the school’s drug prevention program. Additionally, this study may be of interest to other educational leaders, particularly educational leaders from rural areas that are considering adding MRSDT as a part of their drug prevention program